A copper paste with oxidation resistance and preparation method thereof
By adding organic phosphine compounds as antioxidants to the copper slurry, the problem of easy oxidation of copper slurry is solved, significantly improving its antioxidant and conductive properties, and extending its service life.
Patent Information
- Application Number
- CN202211579152.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-05
AI Technical Summary
Copper slurry is prone to oxidation, resulting in reduced conductivity, limiting its application in electronics, semiconductors and solar cells.
By adding organic phosphine compounds as antioxidants, they are tightly coated on the copper surface to form P-C bonds, and the antioxidant properties are enhanced.
Effectively prevent copper oxidation, improve the antioxidant performance of copper slurry, thereby maintaining conductive properties and extending service life.
Smart Images

Figure CN115985550B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive pastes, and in particular to an anti-oxidative copper paste and a method for preparing the anti-oxidative copper paste. Background Art
[0002] In recent years, conductive metal paste has been widely used in semiconductor, electronics, energy, automobile and other fields. It is mainly composed of the following three parts: conductive phase, binder phase and organic carrier. Among them, the conductive phase determines the basic properties of the conductive paste and affects the physical and mechanical properties of the paste product. The conductive phase is usually metal particles, alloy particles and their mixtures; the role of the binder phase is to make the conductive paste film layer firmly bonded to the base material, usually organic binder or inorganic binder, such as epoxy resin; the organic carrier is a mixture of organic polymers, surfactants, dispersants, thixotropic agents and solvents, which is the carrier of the conductive phase and the binder phase, used to wet and disperse the conductive phase particles and regulate the rheological properties of the conductive paste.
[0003] At present, the mainstream market mainly uses silver powder as a conductive filler to prepare conductive paste, and silver paste has excellent conductivity and oxidation resistance. However, silver is expensive, which greatly hinders the widespread application and development of silver paste. The conductivity of copper is second only to silver and is relatively cheap. It has certain applications in electronic packaging and electronic components, such as copper as the terminal electrode of multilayer ceramic capacitors and circuit boards (DBC, Direct Bonded Copper) made of copper paste and ceramic substrates. However, copper is easily oxidized in the air and easily forms an oxide film layer on the surface. The resistivity of the oxide film layer is large, and the conductive performance is reduced, which greatly reduces its practicality. The easy oxidation property of copper has become a bottleneck in the development of copper paste.
[0004] Due to its advantage of low power generation cost, crystalline silicon solar cells are currently widely used. As a conductive material for photovoltaic cells, the amount of silver used has also begun to attract attention. If copper paste with lower cost can be used instead of silver paste as a conductive material for solar cells, it will further promote the application of photovoltaic power generation. Photovoltaic heterojunction cells are a new technology for photovoltaic power generation. Reducing the amount of low-temperature silver paste used in heterojunction cells is currently the key to reducing costs. If low-temperature copper paste can be used instead of low-temperature silver paste, the cost of photovoltaic power generation will be further reduced.
[0005] In view of this, those skilled in the art have made many efforts to improve the antioxidant properties of copper paste. In recent years, some technicians in this field have proposed that the antioxidant properties of copper paste can be achieved by adding antioxidants, and the antioxidants are tightly coated on the surface of copper, thereby reducing the chance of oxygen contacting copper and being oxidized. Chinese invention patent CN115116650A discloses a conductive copper paste, characterized in that it includes copper powder, resin and antioxidant, wherein the antioxidant is a compound containing phosphorus, and the compound containing phosphorus is an inorganic phosphorus-containing compound or an organic phosphorus-containing compound, wherein the organic phosphorus-containing compound is selected from monobasic phosphate, monobasic hypophosphite, polybasic phosphate or polybasic phosphite, preferably monobasic phosphate. This type of organic phosphorus-containing compound has a PO bond, which can be adsorbed on the surface of copper powder to form a phosphorus-containing compound molecular film layer, thereby blocking the oxidative corrosion of water, oxygen and other substances on copper powder. However, practice shows that the functional group length of PO is short and cannot be densely distributed on the surface of copper, so the antioxidant performance is not as expected. Summary of the invention
[0006] In view of the defects in the prior art, the purpose of the present invention is to provide a copper paste with antioxidant properties, and correspondingly provide a method for preparing the copper paste with antioxidant properties, by adding an antioxidant substance - an organic phosphine compound, so that copper is not oxidized.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:
[0008] A copper paste with oxidation resistance comprises the following raw material components: copper powder, a binder, an organic carrier and an antioxidant, wherein the antioxidant is an organic phosphine compound.
[0009] Preferably, the organic phosphine compound is any one or more of diphosphonic acid, triphosphonic acid, methylenephosphonic acid or carboxylic acid phosphonic acid.
[0010] Preferably, the organic phosphine compound is any one or more of aminotrimethylphosphonic acid (ATMP), ethylenediaminetrimethylphosphonic acid (EDTMP), hydroxyethyldiphosphonic acid (HEDP), diethylenetriaminepentamethylphosphonic acid (DTPMP), and phosphonic acid butanetricarboxylic acid (PBTCA).
[0011] Preferably, the organic phosphine compound is an organic phosphonate.
[0012] Preferably, the organic phosphonate is aminotrimethylphosphonic acid sodium salt.
[0013] Preferably, the organic phosphine compound is an organic phosphonate.
[0014] Preferably, the organic phosphonate is diethyl ethylphosphonate.
[0015] Preferably, the binder is a resin, and the resin is any one or more of epoxy resin, silicone, acrylic acid, and polyurethane.
[0016] Preferably, the organic carrier comprises a curing agent, a thixotropic agent, a dispersant and a solvent, and the solvent is any one or more of polyols, alcohol esters and fatty acids.
[0017] Preferably, based on the total weight of the antioxidant copper paste as 100%, the weight fraction of copper powder is 50% to 95%, the weight fraction of the binder is 0.2% to 20%, the weight fraction of the organic carrier is 0.1% to 40%, and the weight fraction of the antioxidant is 0.1% to 10%.
[0018] A method for preparing an anti-oxidative copper slurry comprises the following steps:
[0019] S1. Remove oxides and organic impurities on the surface of copper powder;
[0020] S2, mixing copper powder, a binder, an organic carrier and an antioxidant and dispersing them evenly to obtain the copper slurry with antioxidant properties; the antioxidant is an organic phosphine compound.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The antioxidant copper paste provided by the present invention comprises an antioxidant substance, namely an organic phosphine compound. The organic phosphine compound has a PC bond. Compared with an organic phosphoric acid compound containing a PO bond, the length of the functional group is increased, so that the phosphorus-containing functional group is better arranged with the copper surface, thereby better protecting the copper from oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0024] Figure 1 The performance test results of Example 1 and Comparative Example 1 are shown in FIG.
[0025] Figure 2 It is a performance test result diagram of Example 2 and Comparative Example 2. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0027] Therefore, the following detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0028] In addition, the materials, reagents, etc. used in the following examples can be obtained from commercial sources unless otherwise specified; the implementation methods used in the following examples are all conventional methods unless otherwise specified.
[0029] According to one aspect of the present invention, a copper paste with antioxidant properties is provided. The copper paste comprises the following raw material components: copper powder, a binder, an organic carrier and an antioxidant, wherein the antioxidant is an organic phosphine compound.
[0030] Specifically, the organic phosphine compound can be any one or more of diphosphonic acid, triphosphonic acid, methylene phosphonic acid or carboxylic acid phosphonic acid. For example, the organic phosphine compound is any one or more of aminotrimethylphosphonic acid (ATMP), ethylenediaminetrimethylphosphonic acid (EDTMP), hydroxyethyldiphosphonic acid (HEDP), diethylenetriaminepentamethylphosphonic acid (DTPMP), phosphonic acid butanetricarboxylic acid (PBTCA).
[0031] In addition, the organic phosphine compound may also be an organic phosphonate, such as aminotrimethylphosphonic acid sodium salt; or an organic phosphonate ester, such as diethyl ethylphosphonate.
[0032] Furthermore, a resin can be used as a binder, and the resin can be any one or more of epoxy resin, silicone, acrylic or polyurethane; in addition, the organic carrier can include a thixotropic agent, a dispersant and a solvent, wherein the solvent is any one or more of polyols, alcohol esters or fatty acids.
[0033] Furthermore, as a preferred embodiment, based on the total weight of the antioxidant copper paste as 100%, the weight fraction of the copper powder is 50% to 95%, the weight fraction of the binder is 0.2% to 20%, the weight fraction of the organic carrier is 0.1% to 40%, and the weight fraction of the antioxidant is 0.1% to 10%.
[0034] According to another aspect of the present invention, there is provided a method for preparing a copper slurry having oxidation resistance, comprising the following steps:
[0035] S1. Remove oxides and organic impurities on the surface of copper powder;
[0036] S2, mixing copper powder, a binder, an organic carrier and an antioxidant and dispersing them evenly to obtain the copper paste with antioxidant properties; wherein the antioxidant is an organic phosphine compound.
[0037] The organic phosphine compound may be any one or more of diphosphonic acid, triphosphonic acid, methylenephosphonic acid or carboxylic acid phosphonic acid. For example, the organic phosphine compound is any one or more of aminotrimethylphosphonic acid (ATMP), ethylenediaminetrimethylphosphonic acid (EDTMP), hydroxyethyldiphosphonic acid (HEDP), diethylenetriaminepentamethylphosphonic acid (DTPMP), phosphonic acid butanetricarboxylic acid (PBTCA). In addition, the organic phosphine compound may also be an organic phosphonate, such as aminotrimethylphosphonic acid sodium salt; or an organic phosphonate, such as diethyl ethylphosphonate.
[0038] Furthermore, the antioxidant copper paste claimed in the present application has no restrictions on the raw material component, copper powder. The copper powder that can be used for thick film paste is generally in the micron level, that is, the average particle size of the copper powder is between 0.1 and 100 microns; more generally, the average particle size is between 0.5 and 10 microns. For example, the product of Japan Tonghe Holdings (Group) Co., Ltd. (product code 6B, hereinafter referred to as "copper powder 6B") can be selected. The average particle size of copper powder 6B is 3.7 microns, and the typical oxygen content is 0.39%.
[0039] Before preparing the copper slurry with antioxidant properties, the copper powder is pretreated. For example, 100 grams of copper powder can be placed in 500 milliliters of aqueous solution containing 4 milliliters of sulfuric acid (sulfuric acid: water = 1:1) and stirred to remove the oxide on the surface of the copper powder, and then dried in a vacuum to reduce the typical oxygen content to below 0.1%.
[0040] Then, the treated copper powder is used to prepare a low-temperature curing slurry. According to the type of resin, the low-temperature curing slurry can be divided into epoxy resin, silicone, acrylic acid and polyurethane. The low-temperature curing slurry can contain one or more resins, which generally also contain a curing agent. The curing agent cures the low-temperature slurry into an application state through the polymerization reaction of the resin. It should be noted that the so-called low-temperature curing is relative to high-temperature sintering. Usually the high-temperature sintering temperature is around 850°C, while the low-temperature curing temperature is completed at a temperature of 100 to 300°C.
[0041] Furthermore, a typical low-temperature curing slurry usually also contains a solvent suitable for the application, and typical solvents include polyols, alcohol esters, and fatty acids, etc. In addition, the low-temperature curing slurry may also contain a thixotropic agent and a dispersant.
[0042] The following is a description of the beneficial effects of the embodiments of the present invention compared with the prior art using specific test data.
[0043] In the following embodiments, the copper powder used is the copper powder 6B mentioned above, with an average particle size of 3.7 microns and a typical oxygen content of 0.39%; the epoxy resin used is the epoxy resin with the commercial name EPON 828; and the curing agent used is the curing agent with the commercial name Epicure.
[0044] Example 1
[0045] (1) Pretreatment of copper powder
[0046] 100 g of copper powder 6B was placed in 500 ml of aqueous solution containing 4 ml of sulfuric acid (sulfuric acid: water = 1:1) and stirred to remove oxides on the surface of copper powder 6B, and then dried in a vacuum to reduce the typical oxygen content to below 0.1%.
[0047] (2) Preparation of epoxy resin low-temperature conductive copper paste P1
[0048] Referring to Table 1, 100 g of conductive copper paste raw materials were weighed, including: 6.5 g of Epon 828 epoxy resin, 2.8 g of Epicure curing agent, 3.4 g of butyl carbitol, 0.2 g of dispersant, 0.1 g of acetic acid, 0.5 g of aminotrimethylenephosphonic acid and 86.5 g of treated copper powder 6B. The above raw materials were mixed at high speed and rolled with a three-roll mill to a fineness of less than 18 to obtain the epoxy resin low-temperature conductive copper paste P1 of Example 1.
[0049] Comparative Example 1
[0050] (1) Pretreatment of copper powder
[0051] 100 g of copper powder 6B was placed in 500 ml of aqueous solution containing 4 ml of sulfuric acid (sulfuric acid: water = 1:1) and stirred to remove oxides on the surface of copper powder 6B, and then dried in a vacuum to reduce the typical oxygen content to below 0.1%.
[0052] (2) Preparation of epoxy resin low-temperature conductive copper paste D1
[0053] The composition ratio of Comparative Example 1 is basically the same as that of Example 1, except that the organic phosphine compound aminotrimethylenephosphonic acid is not added in Comparative Example 1. Specifically, referring to Table 1, 100g of conductive copper paste raw materials are weighed, including: 6.5g of Epon 828 epoxy resin, 2.8g of Epicure curing agent, 3.9g of butyl carbitol, 0.2g of dispersant, 0.1g of acetic acid and 86.5g of treated copper powder 6B. After the above raw materials are mixed at high speed, they are rolled with a three-roll mill to a fineness of less than 18 to obtain the epoxy resin low-temperature conductive copper paste D1 of Comparative Example 1.
[0054] Table 1
[0055] Components Example 1 Comparative Example 1 Epon 828 epoxy resin 6.5g 6.5 Epicure Hardener 2.8g 2.8 Butylcarbitol 3.4g 3.9 Dispersants 0.2g 0.2 Acetic acid 0.1g 0.1 Aminotrimethylenephosphonic acid 0.5g 0 Copper powder 6B (after treatment) 86.5g 86.5
[0056] Example 2
[0057] (1) Pretreatment of copper powder
[0058] 100 g of copper powder 6B was placed in 500 ml of aqueous solution containing 4 ml of sulfuric acid (sulfuric acid: water = 1:1) and stirred to remove oxides on the surface of copper powder 6B, and then dried in a vacuum to reduce the typical oxygen content to below 0.1%.
[0059] (2) Preparation of polyurethane low-temperature conductive copper paste P2
[0060] Referring to Table 2, 100 g of conductive copper paste raw materials were weighed, including: 24 g of polyurethane dispersion, 1.0 g of dispersant, 0.1 g of acetic acid, 1.0 g of aminotrimethylenephosphonic acid, and 73.9 g of treated copper powder 6B. The above raw materials were mixed at high speed and rolled with a three-roll mill to a fineness of less than 18 to obtain the polyurethane low-temperature conductive copper paste P2 of Example 2.
[0061] Comparative Example 2
[0062] (1) Pretreatment of copper powder
[0063] 100 g of copper powder 6B was placed in 500 ml of aqueous solution containing 4 ml of sulfuric acid (sulfuric acid: water = 1:1) and stirred to remove oxides on the surface of copper powder 6B, and then dried in a vacuum to reduce the typical oxygen content to below 0.1%.
[0064] (2) Preparation of polyurethane low-temperature conductive copper paste D2
[0065] The composition ratio of Comparative Example 2 is basically the same as that of Example 2, except that the organic phosphorus compound aminotrimethylenephosphonic acid is not added in Comparative Example 2, but oleic acid is added. Specifically, referring to Table 2, 100g of conductive copper paste raw materials are weighed, including: 24g of polyurethane dispersion, 1.0g of dispersant, 0.1g of acetic acid, 1.0g of oleic acid, and 73.9g of copper powder 6B. After the above raw materials are mixed at high speed, they are rolled with a three-roll mill to a fineness of less than 18 to obtain the polyurethane low-temperature conductive copper paste D2 of Comparative Example 2.
[0066] Table 2
[0067]
[0068]
[0069] Performance Testing
[0070] The epoxy resin low-temperature conductive copper paste P1 prepared in Example 1 and the epoxy resin low-temperature conductive copper paste D1 prepared in Comparative Example 1 were printed on an alumina substrate in a serpentine shape, dried at 100°C for 1 hour, and then cured at 250°C for 20 minutes. Furthermore, at 200°C, the change in the resistance of the serpentine line over time was tested, and the results were as follows: Figure 1 shown.
[0071] Example 1 added aminotrimethylenephosphonic acid, an organic phosphonic acid, as an antioxidant, while Comparative Example 1 did not add an organic phosphonic acid compound. Figure 1 The data show that the addition of organic phosphine compounds can more effectively prevent the oxidation of low-temperature copper paste.
[0072] Similarly, the polyurethane low-temperature conductive copper paste P2 prepared in Example 2 and the polyurethane low-temperature conductive copper paste D2 prepared in Comparative Example 2 were printed on an alumina substrate in a serpentine shape, dried at 100°C for 1 hour, and then cured at 150°C for 20 minutes. Furthermore, at 150°C, the change in the resistance of the serpentine line over time was tested. The results are shown in FIG. Figure 2 shown.
[0073] Example 2 adds aminotrimethylenephosphonic acid as an antioxidant, while Comparative Example 2 replaces the aminotrimethylenephosphonic acid in Example 2 with oleic acid which also has an antioxidant effect. Figure 2 The data still show that the addition of organophosphine compounds can more effectively prevent copper oxidation.
[0074] The above describes the specific embodiments of the present invention. Based on the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention.
Claims
1. A copper paste with oxidation resistance, characterized in that: The method comprises the following raw material components: copper powder, a binder, an organic carrier and an antioxidant, wherein the antioxidant is an organic phosphine compound; The organic phosphine compound is an organic phosphonate; The organic phosphonate is diethyl ethylphosphonate.
2. The anti-oxidation copper paste according to claim 1, characterized in that: The binder is a resin, and the resin is any one or more of epoxy resin, silicone, acrylic acid, and polyurethane.
3. The anti-oxidation copper paste according to claim 1, characterized in that: The organic carrier comprises a curing agent, a thixotropic agent, a dispersant and a solvent, and the solvent is any one or more of polyols, alcohol esters and fatty acids.
4. The anti-oxidation copper paste according to claim 1, characterized in that: Taking the total weight of the anti-oxidation copper paste as 100%, the weight fraction of copper powder is 50% to 95%, the weight fraction of binder is 0.2% to 20%, the weight fraction of organic carrier is 0.1% to 40%, and the weight fraction of antioxidant is 0.1% to 10%.
5. A method for preparing an oxidation-resistant copper paste, characterized in that: The steps include: S1. Remove oxides and organic impurities on the surface of copper powder; S2, mixing copper powder, a binder, an organic carrier and an antioxidant and dispersing them evenly to obtain the copper slurry with antioxidant properties; the antioxidant is an organic phosphine compound, the organic phosphine compound is an organic phosphonate, and the organic phosphonate is diethyl ethylphosphonate.
Citation Information
Patent Citations
Corrosion proteciton of bronzes
CN101809199A
Copper-plated copper surface antioxidation fluid and preparation method
CN109295449A
Conductive copper paste, electrode and preparation method of conductive copper paste
CN115116650A